Country fair cowboy - Curtis, Melinda (Romance fiction writer) (Cowboy academy, 2025)
Dr. Wylie Newland loves being a vet, loves cheery Clementine, Oklahoma, but his crush on Dr. Hazel Hughes is a problem. The new resident has made it clear she's a city girl at heart and won't be staying. Working hand in hand at the fair is bringing them closer...and, hopefully, winning her over. Sure, Hazel is beginning to see that Wylie is pretty great, but he's also stuck in many regards. With Hazel showing him new ways to look at the world, and Wylie showing her that settling down isn't settling for less, could they take first prize for romance?